Influenza in Brazil: surveillance pathways - Cantarino, Ligia; Merchan-Hamann, Edgar (The Journal of Infection in Developing Countries, 2016)
Influenza is a viral disease of global concern that has demanded the attention of health authorities. Since 1947, as a preventive measure, the World Health Organization monitors viral circulation to define the annual vaccine through a worldwide network of laboratories. This article presents the structuring of influenza surveillance in Brazil and highlights virological surveillance and the role of diagnostic laboratories as well as the expansion of actions to improve detection and expedite responses. The model set corresponds to sentinel surveillance complemented by the universal notification of severe acute respiratory syndrome investigating outbreaks, deaths, and unusual events and monitoring hospitalization and mortality in an expanded surveillance. In this review, we address aspects of influenza surveillance in animals, the need for interagency integration, and the sharing of information in many surveillance systems.